2022
DOI: 10.1007/s00018-022-04297-z
|View full text |Cite
|
Sign up to set email alerts
|

Sulfavant A as the first synthetic TREM2 ligand discloses a homeostatic response of dendritic cells after receptor engagement

Abstract: Objective The immune response arises from a fine balance of mechanisms that provide for surveillance, tolerance, and elimination of dangers. Sulfavant A (SULF A) is a sulfolipid with a promising adjuvant activity. Here we studied the mechanism of action of SULF A and addressed the identification of its molecular target in human dendritic cells (hDCs). Methods Adjuvant effect and immunological response to SULF A were assessed on DCs derived from hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…One of the best-known examples of these mechanisms is the interaction of the costimulatory molecule CD28 and the inhibitory counterpart CTLA-4 along with their ligands CD80 and CD86 (25) (26). SULF A is a small organic molecule suitable for pharmaceutical applications due to the property of triggering an unconventional maturation of DCs and initiating an effective immune response in vivo (11) (14). In this study we showed that SULF A can modulate DC-T cell synapse in the context of the allogeneic MLR.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…One of the best-known examples of these mechanisms is the interaction of the costimulatory molecule CD28 and the inhibitory counterpart CTLA-4 along with their ligands CD80 and CD86 (25) (26). SULF A is a small organic molecule suitable for pharmaceutical applications due to the property of triggering an unconventional maturation of DCs and initiating an effective immune response in vivo (11) (14). In this study we showed that SULF A can modulate DC-T cell synapse in the context of the allogeneic MLR.…”
Section: Discussionmentioning
confidence: 59%
“…In this study we showed that SULF A can modulate DC-T cell synapse in the context of the allogeneic MLR. According to the previous reports (14), addition of SULF A to MLR determined DC maturation after 48h with increased expression of the costimulatory molecules ICOSL and OX40L in conjunction with down-regulation of cytokine IL-12 and up-regulation of IL-10. This condition led to additional T cell proliferation and, although T CD4+ and T CD8+ subsets were both promoted, it was skewed towards T CD4+ proliferation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Triggering receptor expressed on myeloid cells 2 (TREM2) is a transmembrane receptor of the immunoglobulin superfamily that binds an array of ligands including bacteria and polyanionic molecules (1), DNA (2), lipoproteins (3), phospholipids (4) and sulfoglicolipids such as Sulfavant A (5). TREM2 itself does not contain intrinsic signaling capabilities; therefore, it associates with the adaptor proteins DNAX activation protein (DAP) 12 and DAP10; which, upon TREM2-ligand interaction are phosphorylated and propagate signals within the cell (6).…”
Section: Introductionmentioning
confidence: 99%